Biological indicators of aquatic health: Evaluating water quality in Krueng Baru River - AG, Burhanuddin; Elvitriana, Elvitriana; Andalia, Nurlena; Sariakin, Sariakin; Ridhwan, Muhammad (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The purpose of this study was to determine the quality of water contained in the Krueng Baru River area, South Aceh Regency, and to determine the effect of iron metal (Fe) pollution on the structure of snail shells found in the Krueng Baru River area, South Aceh Regency. This research was conducted on February 20/March 2021. Research sampling in the Krueng Baru River, South Aceh Regency. Ferrous heavy metals (Fe) were analyzed at the Chemistry Laboratory and Biological Laboratory of Syiah Kuala University. The research site contained research samples of suction snails (Cerithidea obtusa). The sampling technique uses a purposive sampling technique. The data processing method used in the research is the descriptive method. Based on the results of research that have been done, Fe heavy metal levels in water and biological indicators of Cerithidea obtusa at station I 1,264 ppm, station III 2,323 ppm, and most obtained at station II with an average amount of Fe levels reaching 2,592 ppm. Based on the results of the analysis, in terms of the biological indicators of the sucker Cerithidea obtusa, it shows that there are differences in water quality at Station I, Station II and Station III. Conclusions based on the results of research on water quality in the Krueng Baru River show the content of heavy metal compounds (Fe) in the river, which means the area is polluted with Fe.